2019
DOI: 10.1038/s41467-019-11749-x
|View full text |Cite
|
Sign up to set email alerts
|

Enabling long-lived organic room temperature phosphorescence in polymers by subunit interlocking

Abstract: Long-lived room temperature phosphorescence (LRTP) is an attractive optical phenomenon in organic electronics and photonics. Despite the rapid advance, it is still a formidable challenge to explore a universal approach to obtain LRTP in amorphous polymers. Based on the traditional polyethylene derivatives, we herein present a facile and concise chemical strategy to achieve ultralong phosphorescence in polymers by ionic bonding cross-linking. Impressively, a record LRTP lifetime of up to 2.1 s in amorphous poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
175
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(178 citation statements)
references
References 42 publications
2
175
0
1
Order By: Relevance
“…Currently, the development of smart luminescent materials with tunable multicolor emission upon external stimuli, such as temperature, light, electric/magnetic eld, excitation intensity and pressure, is receiving increasing attention because of their unique photophysical properties and potential applications in information encryption, visual detection of UV lights, anticounterfeiting, sensing and bioassays. [1][2][3][4][5][6][7][8] Thus far, despite the fact that multicolor luminescence has been successfully achieved through the modulation of crystallinity, molecular conformation/packing and composition of the compounds, or the combination of different emitters, [5][6][7][8][9][10][11][12][13] it remains challenging to realize the tunability of persistent phosphorescence in pure organic single-component systems, [14][15][16][17][18][19][20] particularly in single crystals. 14 While there is growing interest in the achievement of pure organic persistent room temperature phosphorescence (p-RTP), [21][22][23][24][25][26][27] little attention has been given to its tunability, [14][15][16][17][18][19][20] presumably because of the high susceptibility of triplets 28-38 and the difficulty in the construction of diverse triplet emissive populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the development of smart luminescent materials with tunable multicolor emission upon external stimuli, such as temperature, light, electric/magnetic eld, excitation intensity and pressure, is receiving increasing attention because of their unique photophysical properties and potential applications in information encryption, visual detection of UV lights, anticounterfeiting, sensing and bioassays. [1][2][3][4][5][6][7][8] Thus far, despite the fact that multicolor luminescence has been successfully achieved through the modulation of crystallinity, molecular conformation/packing and composition of the compounds, or the combination of different emitters, [5][6][7][8][9][10][11][12][13] it remains challenging to realize the tunability of persistent phosphorescence in pure organic single-component systems, [14][15][16][17][18][19][20] particularly in single crystals. 14 While there is growing interest in the achievement of pure organic persistent room temperature phosphorescence (p-RTP), [21][22][23][24][25][26][27] little attention has been given to its tunability, [14][15][16][17][18][19][20] presumably because of the high susceptibility of triplets 28-38 and the difficulty in the construction of diverse triplet emissive populations.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, tunable multicolor persistent phosphorescence from pure organics has been observed in certain nonaromatic luminophores, [18][19][20] aromatic crystals 14 and ionized or doped polymers, [15][16][17] at cryogenic temperatures (i.e., 77 K) and/or even under ambient conditions. For example, Huang and co-workers demonstrated tunable p-RTP in 2,4,6-trimethoxy-1,3,5-triazine (TMOT) crystals, 14 and Zhao et al reported a tunable aerglow from blue to red by tuning the aggregation state of pyrene derivatives in poly(vinyl alcohol) (PVA) lms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yuan and co‐workers first reported that ionization provided a set of nonaromatic polymers with enhanced phosphorescence based on a clustering‐triggered emission mechanism owing to the stiffening of conformations through the electrostatic interaction . Our group also prepared a series of aromatic polystyrene derivatives with ultralong phosphorescence (UOP) by subunit interlocking with different metal ions, and a record UOP lifetime of up to 2.1 s was achieved . Nevertheless, new purely organic phosphorescence polymers still need to be discovered owing to the urgent need to expand the scope of RTP materials for potential applications in photonics fields.…”
Section: Figurementioning
confidence: 99%
“…Unlike others, the PL signal requires speci c excitation, which therefore guarantees advanced data con dentiality in anti-counterfeit and optical encryption applications. Among all reported PL materials, the materials with long afterglow features show very unique persistent luminescence with signi cantly prolonged lifetimes (ms~s), which enables naked-eye observation of their delayed emission with enhanced signal-to-noise ratio [18][19][20][21][22][23][24] . Despite their fascinating properties, long afterglow materials with PIOM characters are still rarely reported.…”
Section: Introductionmentioning
confidence: 99%